Coagulation Disorders and Bleedings in Critically Ill Patients With Hemophagocytic Lymphohistiocytosis. Issue 40 (October 2015) - Valade, Sandrine; Azoulay, Elie; Galicier, Lionel; Boutboul, David; Zafrani, Lara; Stepanian, Alain; Canet, Emmanuel; Lemiale, Virginie; Venot, Marion; Veyradier, Agnès; Mariotte, Eric
Abstract : Abstract: Reactive hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition related to a cytokine storm leading to multiorgan dysfunction. A better understanding of coagulation disorders, frequently reported in HLH patients, may improve outcomes. Critically ill HLH patients managed in a multidisciplinary national reference center were retrospectively included. Relationships between coagulation disorders, severe bleedings, and outcomes were assessed. One hundred and seventeen patients fulfilled the HLH 2004 criteria. The most common HLH etiology was hematologic conditions (73%), followed by infectious diseases (20%), systemic rheumatic diseases (5%), and undetermined HLH etiology (3%). All patients exerted thrombocytopenia. Coagulation disorders were diagnosed in 79 (68%) patients (61 had hypofibrinogenemia < 1.5 g/L, 51 had prothrombin time [PT] < 50%). The worst median value throughout ICU stay was 52% (38–65) for PT with a factor V level of 35% (27–43), 1.59 (1.30–2.09) for the activated partial thromboplastin time (APTT) ratio, and 2.33 g/L (1.13–3.86) for the fibrinogen level. Disseminated intravascular coagulation (DIC) was found in 50% of patients. Coagulation disorders were more frequent in immunocompromised patients, those with histological/cytological feature of hemophagocytosis, those with the highest ferritin concentrations, and in patients with HLH not related to infection. These patients were more prone to receive mechanical ventilation, vasopressors, or renal replacement therapy. Twenty-six (22%) patients presented severe bleeding complications, including 5 patients dying from hemorrhagic shock. Strikingly, the only coagulation parameter significantly associated with severe bleeding was low fibrinogen with a cutoff value of 2 g/L ( P  = 0.03). Overall, 33 (28%) patients died in the ICU and hospital mortality was 44%. Coagulation disorders were associated with higher mortality, especially fibrinogen < 2 g/L ( P  = 0.04) and PT value ( P  = 0.03). The occurrence of bleeding complications was not associated with higher risk of hospital death. Risk factors associated with mortality by multivariate analysis were fibrinogen level < 2 g/L (OR 2.42 [1.08–5.41]), SOFA score > 6 (OR 3.04 [1.32–6.98]), and age > 46 years (OR 2.26 [1.02–5.04]). Up to two-third of critically ill HLH patients present with coagulation disorders. Hypofibrinogenemia or DIC was found in half of the patients and low PT in 40%. These patients require more life support and have a higher mortality rate. Fibrinogen <2 g/L is associated with the occurrence of severe bleeding and mortality.